Steps of the development of cervical cancer cytological screening - Mazitova M.I; M.S. Bikeneev (LCC «Medicine-Inform», 2019)
M.I. Mazitova1, M.S. Bikeneev2 1 Kazan State Medical Academy - Branch of the Russian Medical Academy of Continuous Vocational Education, Kazan, Russian Federation 2 City Clinical Hospital No. 7, Kazan, Russian Federation Cervical cancer is one of the five most common cancers and ranks fifth among gynecological disorders. Pathogenesis of cervical cancer has been well-studied and is regarded as consistent multistep process. Early diagnosis of cervical cancer is one of the most important issues in obstetrics and gynecology. The paper addresses the history of cytological screening of cervical cancer, the application of Pap test in various countries, the principles of population screening, and the results of the organization of cervical screening in two regions of the Republic of Tatarstan. The paper also highlights the factors of successful cytological screening, i.e., population coverage, sampling, fixation, staining, and examination techniques, professional skills of cytologist, and frequency of examinations. The efficacy of modern cytological technique, fluid cytology, is assessed as compared with classic cytological screening. Comparative evaluation of various techniques of fluid cytology is a ddressed as well. In conclusion, the paper discusses guidelines on cervical screening in USA and Russia. Cytological techniques are still important while fluid cytological is a reliable screening test. The success of cytological screening depends on several factors, among them, population coverage is the most important one. Currently, the outcome of the fight against cancer is closely associated with early diagnosis and effective treatment for precancerous conditions. Keywords: cervical cancer, cervical dysplasia, cytological examination, cytology, screening, human papillomavirus. For citation: Mazitova M.I., Bikeneev M.S. Steps of the development of cervical cancer cytological screening. Russian Journal of Woman and Child Health. 2019;2(4):322-326.